Structural and functional studies of the Mitochondrial Cysteine Desulfurase from Arabidopsis thaliana - Turowski, Valeria Rosana (2012)
AtNfs1 is the Arabidopsis thaliana mitochondrial homolog of the bacterial cysteine desulfurases NifS and IscS, having an essential role in cellular Fe–S cluster assembly. Homology modeling of AtNfs1m predicts a high global similarity with E. coli IscS showing a full conservation of residues involved in the catalytic site, whereas the chloroplastic AtNfs2 is more similar to the Synechocystis sp. SufS. Pull-down assays showed that the recombinant mature form, AtNfs1m, specifically binds to Arabidopsis frataxin (AtFH). A hysteretic behavior, with a lag phase of several minutes, was observed and hysteretic parameters were affected by pre-incubation with AtFH. Moreover, AtFH modulates AtNfs1m kinetics, increasing Vmax and decreasing the S0.5 value for cysteine. Results suggest that AtFH plays an important role in the early steps of Fe–S cluster formation by regulating AtNfs1 activity in plant mitochondria.